A socio-linguistic theory of closing the gap in Scottish schools - Ian Williams (University of Aberdeen, School of Education, 2021)
Inequality in achievement in Scottish schools is argued to be caused in part by the process through which learning may take place, for example the medium of the Curriculum for Excellence (CfE) Literacy Outcomes. In practice, and perhaps by implication, standard, sequenced middle-class discourse, be it Scots or English, may be presumed to be the assessed process of learning and thus provide a barrier. Alternatives are considered: radical, extra-curricular political groupings, supplemented by social media dialects; direct instruction of information as a stage sequence towards open, group discourse; subversion of standard language through consciousness of a continuum between radical dialect and standard form.